Eksplorasi Work-Life Balance dan Work Engagement Terhadap Kinerja Karyawan PT Bank Rakyat Indonesia (Persero) Tbk. Tasikmalaya - Yuniasih, Yuyun; Munawar, Andri Helmi; Maulana, Ilham Arif; Nafisa, Nayla Azzahra (Program Studi Perbankan dan Keuangan Fakultas Ekonomi Universitas Siliwangi, 2025)
This study aims to answer the following research questions: (1) does work-life balance (WLB) affect employee performance, and (2) does work engagement affect employee performance at PT Bank Rakyat Indonesia (Persero) Tbk Tasikmalaya. The research employed a quantitative approach with an explanatory and cross-sectional design. The population consisted of all employees in the observed branch, totaling 46 persons, who were selected using a saturated sampling technique. Data were collected through a Likert-scale questionnaire measuring WLB, work engagement, and employee performance, and were analyzed using multiple linear regression. The results show that WLB is perceived at a fairly good level, while work engagement and employee performance are at a high level. Inferentially, WLB has a positive and significant effect on employee performance, and work engagement likewise has a positive and significant effect on performance. Simultaneously, WLB and work engagement explain 61.0% of the variance in employee performance, while the remaining 39.0% is influenced by other factors outside the model. These findings indicate that improving employee performance in the banking sector is not only determined by technical aspects of the job, but also by the organization’s ability to create a healthy work-life balance and foster strong work engagement through appropriate human resource management policies and practices.Keywords: work-life balance; work engagement; employee performance.